Propuesta de rehabilitación del conjunto Arquitectonico “señor de la caridad" de la parroquia San Andres. - Avalos Philco, Yanara Estefania (2017)
Those who lives around is influence by the patrimonial architectural set “ Santurio Señor de la Caridad”, located in the parish of San Andrés, Guano city, Chimborazo province and they feel identified with it, it can be for their history, its Constructive system or for the religious, which they had feld the need to proposal for intervetion of this unique space, specifically the old convent, the ruins, green áreas, also as its integration with the new convent and its surroundings, specially to avoíd its deterioration. The proposal is made through the architectural rehabilitation, for it wide development and to form the ntervention, because beyond the material it proposes to dynamize the physical space with the use of the Community museam. The methodology applied is a qualiative approach, through the research – acción, wich it allowed to abtain the results, starting from diagnoses, studying causes, consequenses and solution to the problema; Basing the observation, questions, interviews, workshops; which was carried aut the current anaysis of the status, generating a study of pathologies and the inmediate environment. From this information and the work the actors of the process, it was feasible to propose the use of it, also its hepls to understand the cultural aspects of the place Finally, it is concluded that architectural rehabilitation, in this case, is the most appropriate way of the intervention in the “Santuario Señor de la Caridad”, to the recovery this ptrimonial of the intern¿vention in the “ Santuario Señor de la Caridad”, to the recovery this patrimonial space and to contribution its value.